Pilgrims’ Acceptance of a Mobile App for the Camino de Santiago - Antunes, Angela (2016)
This study aims to identify which factors affect pilgrim’s intentions to use a pilgrimage app, based on the extended unified theory of acceptance and use of technology (UTAUT2).The empirical results were obtained from a sample of 222 pilgrims of the Camino de Santiago (Saint James’s Way). Partial Least Squares Structural Equation Modelling was applied to test the hypothesized relationships of the proposed model. The results indicate that the most important factor affecting intentions to use the app is performance expectancy. Effort expectancy, social influence and hedonic motivations are other determinants of intentions to use a pilgrimage app. Facilitating conditions and habit do not affect intentions to use the app. The results of this study are valuable for a successfully implementation of pilgrimage apps, providing useful insights for pilgrimage app designers.